Trends and evolution mapping of university library collaboration research - Sani Zulviah; Agus Rusmana; Yunus Winoto (Perpustakaan Universitas Gadjah Mada, 2025)
Introduction. Collaboration among libraries is essential for addressing resource and collection limitations, and supporting the optimization of research and technology-based services. Using a bibliometric approach, this study analyzes research performance and science mapping related to university library collaboration Research Methods. This research used a quantitative method and a bibliometric approach, applying the PICO framework search strategy in the Scopus database. The strategy produced two main keywords, “collaboration” and “university libraries.” The initial search yielded 3,424 documents. Based on inclusion and exclusion criteria, the selection process resulted in 2,312 final documents for analysis. The researcher cleaned the metadata using OpenRefine, particularly in the keywords section, to ensure accuracy before analysis. Data Analysis. The analysis used VOSviewer and Biblioshiny to map research performance and science mapping. Results. The findings reveal a fluctuating publication trend, peaking in 2019, with Anglada L identified as the author with the highest citation count. Science mapping indicates five stages of research evolution, focusing on collaboration and cooperation in university libraries. Conclusion. Higher education library collaboration has evolved from traditional services toward technology integration and cross-sector collaboration, with research opportunities in information literacy, digital collection management, and research data management to strengthen its global role.